Pengaruh Komunikasi Interpersonal Orang Tua Terhadap Perilaku Remaja - Jannah F; Tsuwaibatul Aslamiyah; Ach. Baidowi; Yanto; S. Fathiyatul Jannah (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2024)
Abstract The research aims to determine the influence of parental interpersonal communication on adolescent behavior in Dusun Tengah, Tlonto Ares Village, Pamekasan. The research employed a quantitative method through a regression test approach. Data were collected from 56 adolescents through the distribution of questionnaires. Hypothesis testing was conducted using the t-test. The research findings indicate that the correlation coefficient of 0.270 suggests a weak relationship between parental interpersonal communication and adolescent behavior. Hypothesis analysis using the t-test reveals a calculated t-value of 2.06, exceeding the critical t-value of 1.68. Therefore, the proposed hypothesis is accepted based on the criterion that if the calculated t-value is greater than the critical t-value, the hypothesis is accepted. The calculation results show that parental interpersonal communication has a 7.29% influence on adolescent behavior. Keywords: Communication, Parents, Interpersonal, Adolescents